Analysis of Fast Food Brand Preferences using Eye Tracking and Human Information Processing Model - Murni, Indah Puspa; Irfadinata, Tata; Wijayanto, Titis (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Fast food is the most favored food among various age groups, from children to the elderly. There are several well-known fast food brands, such as McDonald's (MCD) and Kentucky Fried Chicken (KFC). Both brands compete in innovating and promoting their products to reach a wide target market and continuously strive to improve the quality of their products. Improved product quality is often achieved through interactions between businesses and consumers via digital marketing. Digital marketing is a medium that can accurately represent consumer needs. One of the methods used in digital marketing is through posters. This is necessary to understand consumers' desires through the thinking process when receiving information from the posters provided. This study involved 20 respondent with an average age of 30.45 ± 8.7 years. These respondent were asked to undergo two data collection processes: eye tracking through a gaze recorder website and questionnaire filling through a provided Google Form. The aim of this research is to determine the fast food brand preferences chosen by respondent based on the information obtained using Eye Tracking and the Human Information Processing Model. The results of this study indicate differences in the outcomes of the dwell time results for each age factor and time spent in AOI did not exhibit significant differences among respondent.